Duration of Early Breastfeeding Initiation for Hypothermia Prevention at Karang Taliwang Health Center in 2024 - Utami, Pramita Putri; Hidayati, Nurul; Supriwandani, Heru (Fakultas Ilmu Kesehatan Universitas Nahdlatul Wathan Mataram, 2025)
One of the advantages of IMD is preventing hypothermia in newborns. Hypothermia contributes to 7% of infant mortality in Indonesia. This is related to the importance of IMD to preventing hypothermia. The purpose of this study was to determine the effectiveness of the duration of Early Breastfeeding Initiation on preventing Hypothermia at the Karang Taliwang Health Center in 2024. The study was conducted in September 2024, the researcher used an observational pre-experimental research design in the form of a design using the One Group Pretest Posttest design. In this study, the sampling technique used was Accidental Sampling. The number of respondents in this study was 14 samples of normal newborns. From the results of the study, was obtained before IMD was carried out, there were 2 samples with hypothermia criteria (14.29%), 12 samples with cold stress criteria (85.71%), and no samples with normal temperature criteria. And the data after early breastfeeding initiation was carried out, there were no respondents with hypothermia criteria (0%), 5 samples with cold stress criteria as many as (35.71%), and 9 samples with normal temperature criteria as many as (64.29%). The results of the Wilcoxon Signed Ranks analysis test 0.002, are smaller than the error limit of α = 0.05, meaning that H1 is accepted and H0 is rejected, which means that the duration of early breastfeeding initiation is effective in preventing hypothermia at the Karang Taliwang Health Center in 2024.